Analysis of SMEs in Cartagena's metal processed products manufacturing subsector - Bedoya Marrugo, Elias Alberto
The companies pymes in the manufacturing of metal products based in the city of Cartagena sector is a sector that has a high fluctuation in the market, whose productive potential is captive by the low level of integration and dynamics between the different companies that make up chain to produce units with a high added value. This article presents an analysis of pymes in the manufacturing subsector of metal products in the city of Cartagena in order to identify weaknesses and opportunities for its improvement in this sector to this end a description of the selected sector was conducted based on visits, interviews and information and then a survey that allowed analyzing the current state of pymes applied.